A high-strength degradable ground film and preparation method thereof

By using modified PBAT materials and additives, crosslinking networks and block copolymer structures are formed, which solves the problem of difficult degradation and poor mechanical properties of traditional mulch materials, and achieves the preparation of mulch with high strength, good anti-aging and moisture retention properties.

CN118930919BActive Publication Date: 2025-04-22SHANDONG BLUE OCEAN CRYSTAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411180893.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-04-22
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

Traditional mulch materials are difficult to degrade, and long-term use will cause pollution to the soil and the environment. At the same time, the linear structure of PBAT materials leads to poor mechanical properties and are susceptible to ultraviolet aging.

Method used

The raw materials of 70-80 parts of PBAT, 3-4.5 parts of additives, 0.3-0.5 parts of additives, 5-10 parts of inorganic filler, 0.5-1.5 parts of antioxidant, 0.1-0.3 parts of antioxidant, and 0.5-1 part of lubricant were used to prepare the plastic film through stirring and twin-screw extrusion mechanism, and the cross-linking network and block copolymer structure were formed through the modification technology of additives one and additives two, thereby improving the mechanical properties and anti-aging ability of the plastic film.

Benefits of technology

It significantly improves the tearing strength and gas barrier effect of the plastic film, enhances moisture retention performance, and effectively improves the anti-ultraviolet aging performance, extending the service life of the plastic film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930919B_ABST
    Figure CN118930919B_ABST
Patent Text Reader

Abstract

The invention relates to the field of material technology, and discloses a high-strength degradable mulch film and a preparation method thereof. The mulch film is made of PBAT as a main raw material, mixed with auxiliary materials such as an auxiliary agent 1 and an auxiliary agent 2, and is made through extrusion granulation and film blowing processes. The auxiliary agent 1 can generate hydrogen bonds with ester groups in PBAT molecular chains. Therefore, during the melting process, the hyperbranched molecular chains on the surface of wollastonite fibers can extend to multiple regions of a PBAT matrix, and generate hydrogen bond association networks with the PBAT molecular chains to form a cross-linked network with the wollastonite fibers as the core, thereby achieving anchoring of the wollastonite fibers and the PBAT matrix, effectively improving the mechanical properties such as tear strength and the gas barrier effect of the PBAT, the auxiliary agent 2 can generate a conjugated effect with the PBAT matrix, and the benzophenone contained in the structure can effectively improve the anti-ultraviolet aging effect of the mulch film, so that the mulch film has a longer service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a high-strength degradable mulch film and a preparation method thereof. Background Art

[0002] With the rapid development of modern agriculture, mulch film, as an important agricultural production material, plays an important role in increasing crop yields and improving soil environment. However, traditional mulch films are mostly made of polymer materials such as polyethylene, which are difficult to degrade. Long-term and large-scale use will cause serious pollution to the soil and environment. Therefore, the development of degradable mulch film has become an important issue for sustainable agricultural development.

[0003] Polybutylene adipate / terephthalate (PBAT) is a thermoplastic biodegradable plastic composed of a copolymer of butylene adipate and butylene terephthalate. As a new type of biodegradable plastic, it has environmentally friendly characteristics, and its processing performance is similar to that of polymer materials such as polyethylene, and it has excellent processing performance, so it has become an ideal material for degradable mulch. However, PBAT itself is a linear semi-crystalline polymer. This structure leads to poor mechanical strength such as tearing. Moreover, since the mulch is laid on the soil surface during use, it will be in direct sunlight for a long time, which requires that the material used to make the mulch has good resistance to ultraviolet aging. However, the PBAT structure contains a large number of aromatic ring-ester conjugated systems, which are easy to absorb ultraviolet rays and cause molecular chain breakage, thereby affecting the service life of the mulch. Therefore, the use of PBAT as a material for making mulch needs to be appropriately improved.

[0004] At present, it is common to improve the comprehensive performance of PBAT by using additives. For example, invention patent CN202211239294.4 discloses a method for preparing a PBAT degradable mulch film, which improves the anti-aging effect of the PBAT mulch film by adding light stabilizers and antioxidants. However, additives such as small molecule light stabilizers actually have serious volatilization and migration phenomena and cannot stay in PBAT for a long time to play a role. Therefore, this modification method actually still has defects. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a high-strength degradable mulch film and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a high-strength degradable mulch film, wherein the mulch film is made of the following raw materials in parts by weight: 70-80 parts of PBAT, 3-4.5 parts of auxiliary agent 1, 0.3-0.5 parts of auxiliary agent 2, 5-10 parts of inorganic filler, 0.5-1.5 parts of antioxidant, 0.1-0.3 parts of antioxidant, and 0.5-1 parts of lubricant;

[0008] The preparation method comprises the following steps:

[0009] T1. Weigh each raw material according to weight.

[0010] T2. Put all the raw materials into a stirring kettle and mix them for 20-40 minutes at a stirring rate of 800-1500r / min to form a uniform material;

[0011] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 150-200°C, the screw speed to 50-100rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0012] T4. Control the screw processing temperature to 130-150℃ and use a film blowing machine to blow the masterbatch into a film.

[0013] As a further embodiment of the present invention, the preparation method of the auxiliary agent 1 comprises the following steps:

[0014] T10, after mixing wollastonite fiber and N,N-dimethylformamide, ultrasonically disperse to form a dispersion, and then shake polyethylene glycol diglycidyl ether and the catalyst, then raise the temperature to 130-140° C., keep it for 2-4 hours under continuous stirring, cool it down, separate, collect the solid matter, and obtain a wollastonite fiber modified body;

[0015] T20. Add the modified wollastonite fiber to toluene and disperse it ultrasonically to form a uniform dispersion. Then add tri(2-aminoethyl)amine to the dispersion and continue stirring. Control the temperature at 60-70°C. After 2-4 hours, add polyethylene glycol diglycidyl ether and continue stirring for 6-9 hours. Cool and discharge the material. Collect the solid by centrifugation.

[0016] As a further embodiment of the present invention, in step T10, the catalyst is stannous chloride.

[0017] As a further embodiment of the present invention, in steps T10 and T20, the number average molecular weight of the polyethylene glycol diglycidyl ether is 1000.

[0018] First, stannous chloride is used as a catalyst to catalyze the ring-opening addition of the silanol groups on the surface of the wollastonite fiber and the glycidyl groups in the structure of polyethylene glycol diglycidyl ether, thereby modifying the polyethylene glycol molecular chain carrying an epoxy group at one end on the surface of the wollastonite fiber to obtain a wollastonite fiber modified body. Then, tri(2-aminoethyl)amine is used as a branching agent to perform a ring-opening addition with the epoxy group at one end of the polyethylene glycol molecular chain, and polyethylene glycol diglycidyl ether is added later, so that the tri(2-aminoethyl)amine in the system and the polyethylene glycol diglycidyl ether perform an uninterrupted ring-opening addition, and finally form a wollastonite fiber with a surface modified with a hyperbranched macromolecular chain, that is, the first auxiliary agent.

[0019] As a further solution of the present invention, the preparation method of the auxiliary agent 2 comprises the following steps:

[0020] T100, mixing the terminal hydrogen-containing silicone oil and 1,4-dioxane evenly to form a mixed solution, then introducing high-purity nitrogen for protection, then adding diallylcarbamoyl chloride to the mixed solution, stirring for 10-20 minutes, controlling the temperature to 70-80°C, adding a platinum catalyst for catalysis, and heat-insulating for 8-12 hours, then evaporating under reduced pressure to remove the solvent, discharging the material, and obtaining a silicone oil block copolymer;

[0021] T200, mix the silicone oil block copolymer and acetone, place in an ice water bath, then add 2,4-dihydroxybenzophenone and the accelerator to the resulting mixture, remove from the ice bath after addition, stir at room temperature for 2-4 hours, and remove the solvent by rotary evaporation to obtain auxiliary agent 2.

[0022] As a further embodiment of the present invention, the average molar mass of the hydrogen-terminated silicone oil is 750 g / mol.

[0023] As a further embodiment of the present invention, the mass of the platinum catalyst added is 0.1-0.3% of the total mass of the hydrogen-terminated silicone oil and diallylcarbamoyl chloride.

[0024] As a further embodiment of the present invention, the accelerator is triethylamine or pyridine.

[0025] Under the catalytic action of the platinum catalyst, the Si-H of the terminal hydrogen-containing silicone oil and the unsaturated olefin group in diallylcarbamoyl chloride undergo silylation reaction to form a silicone oil block copolymer connected end to end. Then, under the action of the promoter, the acyl chloride substituent in the silicone oil block copolymer structure can condense with the hydroxyl group in 2,4-dihydroxybenzophenone, thereby obtaining a silicone oil block copolymer containing a large number of benzophenone ultraviolet absorption functional groups in the structure, namely, auxiliary agent two.

[0026] As a further embodiment of the present invention, the inorganic filler is any one of fumed silica, titanium dioxide, mica powder, calcium carbonate or talc; the antioxidant is any one of antioxidant 168, antioxidant 1076 or antioxidant 1010; and the lubricant is calcium stearate or zinc stearate.

[0027] A high-strength degradable mulch film is prepared by adopting the preparation method.

[0028] Beneficial effects of the present invention:

[0029] (A) The surface of the additive prepared by the present invention contains a large number of active hydroxyl substituents generated by ring opening, which can generate hydrogen bonds with the ester groups in the PBAT molecular chain. Therefore, during the melting process, the hyperbranched molecular chains on the surface of the wollastonite fiber can extend to multiple regions of the PBAT matrix and generate hydrogen bond association networks with the PBAT molecular chains to form a cross-linked network with the wollastonite fiber as the core, thereby achieving the anchoring of the wollastonite fiber and the PBAT matrix, which not only greatly improves the interfacial bonding force between each other, but also can effectively exert the advantages of the wollastonite fiber itself, and effectively improve the mechanical properties of the PBAT such as the tear strength. In addition, due to the presence of the cross-linked network structure, the effect of increasing the cross-linking density of the PBAT matrix can be achieved, so that the compactness of the ground film can be improved, thereby enhancing the gas barrier effect of the ground film, and further improving the moisture retention performance of the ground film.

[0030] (B) The auxiliary agent 2 prepared by the present invention is a block copolymer of silicone oil and benzophenone. During the melting process, the benzene ring in the structure of the auxiliary agent 2 can produce a conjugated effect with the PBAT matrix, so the molecular chains of each other will be entangled and intertwined. The large number of silicon-oxygen bonds in the silicone oil structure can make the ground film decompose and absorb more heat. With a small amount of antioxidant, the thermal oxidation aging phenomenon of the ground film can be effectively improved. In addition, the presence of the benzophenone structure can effectively improve the anti-ultraviolet aging effect of the ground film, so that the ground film has a longer service life.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 This is the infrared analysis test chart of additive 2. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] A high-strength degradable mulch film is made of the following raw materials in parts by weight: 70 parts of PBAT, 3 parts of additive 1, 0.3 parts of additive 2, 5 parts of fumed silica, 0.1 parts of antioxidant 168, and 0.5 parts of calcium stearate;

[0037] The method for preparing the mulch film comprises the following steps:

[0038] T1. Weigh each raw material according to weight.

[0039] T2. Put all the raw materials into a stirring tank and mix them for 40 minutes at a stirring rate of 800r / min to form a uniform material;

[0040] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 160°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0041] T4. Control the screw processing temperature to 130°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0042] The preparation method of auxiliary agent 1 comprises the following steps:

[0043] T10, 3.5 g of wollastonite fiber and N,N-dimethylformamide were mixed and ultrasonically dispersed to form a dispersion, and then 12 g of polyethylene glycol diglycidyl ether with a number average molecular weight of 1000 and 0.2 g of stannous chloride were added and shaken, and then the temperature was raised to 140° C., and maintained for 3 hours under continuous stirring, and then the temperature was lowered, the material was discharged, separated, and the solid matter was collected to obtain a wollastonite fiber modified body;

[0044] T20. Add 3 g of modified wollastonite fiber to toluene and disperse ultrasonically to form a uniform dispersion. Then add 4.5 g of tri(2-aminoethyl)amine to the dispersion and continue stirring. Control the temperature to 65°C. After 2 hours, add 2.4 g of polyethylene glycol diglycidyl ether and continue stirring for 8 hours. Cool and discharge the material. Collect the solid by centrifugation.

[0045] 0.3 g of additive 1 was weighed as a test sample, and the percentage of organic elements in the sample was tested using an organic element analyzer. The results showed that the percentage of carbon element was 27.42%, and the percentage of nitrogen element was 8.39%, wherein the carbon element was provided by polyethylene glycol diglycidyl ether, and the nitrogen element was provided by tri(2-aminoethyl)amine.

[0046] The preparation method of the auxiliary agent 2 comprises the following steps:

[0047] T100, 1.5 g of terminal hydrogen-containing silicone oil with an average molar mass of 750 g / mol was mixed with 1,4-dioxane to form a mixed solution, and then high-purity nitrogen was introduced for protection, and then 0.35 g of diallylcarbamoyl chloride was added to the mixed solution, and after stirring for 15 minutes, the temperature was controlled to 75° C., and 0.002 g of platinum catalyst was added for catalysis. After heat preservation for 9 hours, the solvent was removed by evaporation under reduced pressure, and the material was discharged to obtain a silicone oil block copolymer;

[0048] T200, mix 1.2g of silicone oil block copolymer with acetone, place in an ice water bath, then add 0.2g of 2,4-dihydroxybenzophenone and 0.05g of triethylamine to the resulting mixture, after addition, remove from the ice bath, stir at room temperature for 3h, and remove the solvent by rotary evaporation to obtain auxiliary agent 2.

[0049] The additive 2 was made into potassium bromide tablets and subjected to infrared testing. The results are shown in Figure 1 , analysis shows that 3225cm -1 The absorption peak at 1768 cm is the characteristic absorption peak of the phenolic OH in 2,4-dihydroxybenzophenone. -1 The absorption peak at 1704 cm is the characteristic absorption peak of carbonyl C=O in benzophenone. -1 The absorption peak at 1032 cm is the characteristic absorption peak of the ester group C=O produced by the condensation reaction. -1 The Si-O characteristic absorption peak in silicone oil appeared at the 40°C, and the Si-H characteristic absorption peak did not appear in the spectrum, confirming that the Si-H bond was consumed in the addition reaction.

[0050] Example 2

[0051] A high-strength biodegradable mulch film is made of the following raw materials in parts by weight: 75 parts of PBAT, 4 parts of additive 1, 0.4 parts of additive 2, 6 parts of mica powder, 0.2 parts of antioxidant 1076, and 0.6 parts of calcium stearate;

[0052] The method for preparing the mulch film comprises the following steps:

[0053] T1. Weigh each raw material according to weight.

[0054] T2. Put all the raw materials into a stirring tank and mix them for 30 minutes at a stirring rate of 1000r / min to form a uniform material;

[0055] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 180°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0056] T4. Control the screw processing temperature to 140°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0057] The preparation methods of auxiliary agent 1 and auxiliary agent 2 are shown in Example 1.

[0058] Example 3

[0059] A high-strength degradable mulch film is made of the following raw materials in parts by weight: 80 parts of PBAT, 4.5 parts of auxiliary agent 1, 0.5 parts of auxiliary agent 2, 10 parts of talc powder, 0.3 parts of antioxidant 1010, and 1 part of zinc stearate;

[0060] The method for preparing the mulch film comprises the following steps:

[0061] T1. Weigh each raw material according to weight.

[0062] T2. Put all the raw materials into a stirring tank and mix them for 20 minutes at a stirring rate of 1500r / min to form a uniform material;

[0063] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 200°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0064] T4. Control the screw processing temperature to 150°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0065] The preparation methods of auxiliary agent 1 and auxiliary agent 2 are shown in Example 1.

[0066] Comparative Example 1

[0067] A high-strength degradable ground film is made of the following raw materials in parts by weight: 75 parts of PBAT, 4 parts of wollastonite fiber, 0.4 parts of additive 2, 6 parts of mica powder, 0.2 parts of antioxidant 1076, and 0.6 parts of calcium stearate;

[0068] The method for preparing the mulch film comprises the following steps:

[0069] T1. Weigh each raw material according to weight.

[0070] T2. Put all the raw materials into a stirring tank and mix them for 30 minutes at a stirring rate of 1000r / min to form a uniform material;

[0071] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 180°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0072] T4. Control the screw processing temperature to 140°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0073] The preparation method of the auxiliary agent 2 is shown in Example 1.

[0074] Comparative Example 2

[0075] A high-strength degradable mulch film is made of the following raw materials in parts by weight: 75 parts of PBAT, 0.4 parts of auxiliary agent 2, 6 parts of mica powder, 0.2 parts of antioxidant 1076, and 0.6 parts of calcium stearate;

[0076] The method for preparing the mulch film comprises the following steps:

[0077] T1. Weigh each raw material according to weight.

[0078] T2. Put all the raw materials into a stirring tank and mix them for 30 minutes at a stirring rate of 1000r / min to form a uniform material;

[0079] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 180°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0080] T4. Control the screw processing temperature to 140°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0081] The preparation method of the auxiliary agent 2 is shown in Example 1.

[0082] Comparative Example 3

[0083] A high-strength degradable mulch film is made of the following raw materials in parts by weight: 75 parts of PBAT, 4 parts of additive 1, 6 parts of mica powder, 0.2 parts of antioxidant 1076, and 0.6 parts of calcium stearate;

[0084] The method for preparing the mulch film comprises the following steps:

[0085] T1. Weigh each raw material according to weight.

[0086] T2. Put all the raw materials into a stirring tank and mix them for 30 minutes at a stirring rate of 1000r / min to form a uniform material;

[0087] T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 180°C, the screw speed to 80rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch;

[0088] T4. Control the screw processing temperature to 140°C and use a film blowing machine to blow the masterbatch into a film with a thickness of 20 μm.

[0089] The preparation method of auxiliary agent 1 is shown in Example 1.

[0090] Test Case

[0091] The films in Examples 1 to 3 and Comparative Examples 3 were cut into various test pieces that met the specifications and the following performance tests were performed:

[0092] According to the standard GB / T 1040.3-2006, tensile properties test was carried out;

[0093] According to the standard GB / T 1037-2021, water vapor transmission rate test is carried out;

[0094] According to the standard GB / T 16578.1-2008, tear strength test was carried out;

[0095] Place the test piece in a UV aging acceleration box and set the radiation intensity to 0.68W / m 2 , conduct accelerated UV aging test on the test piece, observe and record the time required for the test piece to turn yellow, and evaluate the anti-UV aging performance. Generally speaking, the longer the time, the better the anti-UV aging performance;

[0096] The test results are recorded in Table 1:

[0097] Table 1 - Test results

[0098]

[0099] The test results show that the film obtained by modifying PBAT with additives 1 and 2 at the same time has high tensile strength and tear strength, good gas barrier properties, good moisture retention effect, and exhibits excellent anti-ultraviolet aging performance.

[0100] However, when the additive was replaced with wollastonite fiber without surface modification, the mechanical properties and gas barrier properties decreased significantly due to poor compatibility with the PBAT matrix and the inability to form a cross-linked network. The mechanical properties of the film prepared without wollastonite fiber were further reduced.

[0101] After removing the second additive, the film loses the protection of the UV absorber, so the anti-ultraviolet aging performance of the film decreases significantly.

[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-strength degradable mulch film, characterized in that: The ground film is made of the following raw materials in parts by weight: 70-80 parts of PBAT, 3-4.5 parts of auxiliary agent 1, 0.3-0.5 parts of auxiliary agent 2, 5-10 parts of inorganic filler, 0.1-0.3 parts of antioxidant, and 0.5-1 parts of lubricant; The preparation method comprises the following steps: T1. Weigh each raw material according to weight. T2. Put all the raw materials into a stirring kettle and mix them for 20-40 minutes at a stirring rate of 800-1500r / min to form a uniform material; T3, feed the material into a twin-screw extruder through a feeding hopper, set the temperature to 150-200°C, the screw speed to 50-100rpm, melt and extrude into strips, and cut into pellets after cooling to form mulch masterbatch; T4, control the screw processing temperature to 130-150℃, and use the film blowing machine to blow the masterbatch into film; The preparation method of the auxiliary agent 1 comprises the following steps: T10, after mixing wollastonite fiber and N,N-dimethylformamide, ultrasonically disperse to form a dispersion, and then shake polyethylene glycol diglycidyl ether and the catalyst, then raise the temperature to 130-140° C., keep it for 2-4 hours under continuous stirring, cool it down, separate, collect the solid matter, and obtain a wollastonite fiber modified body; T20, adding the modified wollastonite fiber to toluene, ultrasonically dispersing to form a uniform dispersion, then adding tri(2-aminoethyl)amine to the dispersion, stirring continuously, and controlling the temperature to 60-70°C, adding polyethylene glycol diglycidyl ether after 2-4 hours, continuing stirring for 6-9 hours, cooling and discharging, and collecting the solid by centrifugation; The preparation method of the auxiliary agent 2 comprises the following steps: T100, mixing the terminal hydrogen-containing silicone oil and 1,4-dioxane evenly to form a mixed solution, then introducing high-purity nitrogen for protection, then adding diallylcarbamoyl chloride to the mixed solution, stirring for 10-20 minutes, controlling the temperature to 70-80°C, adding a platinum catalyst for catalysis, and heat-insulating for 8-12 hours, then evaporating under reduced pressure to remove the solvent, discharging the material, and obtaining a silicone oil block copolymer; T200, mix the silicone oil block copolymer and acetone, place in an ice water bath, then add 2,4-dihydroxybenzophenone and the accelerator to the resulting mixture, remove from the ice bath after addition, stir at room temperature for 2-4 hours, and remove the solvent by rotary evaporation to obtain auxiliary agent 2.

2. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: In step T10, the catalyst is stannous chloride.

3. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: In steps T10 and T20, the number average molecular weight of the polyethylene glycol diglycidyl ether is 1000.

4. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: The average molar mass of the hydrogen-terminated silicone oil is 750 g / mol.

5. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: The mass of the added platinum catalyst is 0.1-0.3% of the total mass of the terminal hydrogen-containing silicone oil and diallylcarbamoyl chloride.

6. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: The accelerator is triethylamine or pyridine.

7. The method for preparing a high-strength degradable mulch film according to claim 1, characterized in that: The inorganic filler is any one of fumed silica, titanium dioxide, mica powder, calcium carbonate or talcum powder; the antioxidant is any one of antioxidant 168, antioxidant 1076 or antioxidant 1010; and the lubricant is calcium stearate or zinc stearate.

8. A high-strength degradable ground film, characterized in that: The method is prepared according to claim 1.

Citation Information

Patent Citations

  • Preparation method of PBAT degradable mulching film

    CN115477832A